1998
DOI: 10.1164/ajrccm.158.3.9712125
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of HLA Genes to Genetic Predisposition in Diffuse Panbronchiolitis

Abstract: Diffuse panbronchiolitis (DPB) in East Asia is a distinctive chronic obstructive pulmonary disease of unknown etiology. We hypothesize that the disease susceptibility is due to genetic predisposition unique to Asians. Association between human leukocyte antigen (HLA)-Bw54 and the disease was previously reported. In the present study, using newly developed polymerase chain reaction (PCR)- based methods, we directly analyzed HLA class I and II alleles in 76 Japanese patients. HLA-A, -B, and -C antigens were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 20 publications
6
38
1
1
Order By: Relevance
“…However, the cold hemagglutinin (CHA) titer was only 17.6% of positive in our DPB patients, suggesting that the CHA titer might not be as important for the diagnosis of Chinese DPB patients as it for Japanese (27,43). Additionally, positive HLA-BW54 was only detected in 3 of 12 (25.0%) patients in this group, suggesting that the relationship between HLA-BW54 and Chinese DPB patients might not correlate as well as with Japanese DPB patients (44). Among diagnostic tests, a chest CT scan provides the most valuable diagnostic means for such patients.…”
Section: Discussionmentioning
confidence: 73%
“…However, the cold hemagglutinin (CHA) titer was only 17.6% of positive in our DPB patients, suggesting that the CHA titer might not be as important for the diagnosis of Chinese DPB patients as it for Japanese (27,43). Additionally, positive HLA-BW54 was only detected in 3 of 12 (25.0%) patients in this group, suggesting that the relationship between HLA-BW54 and Chinese DPB patients might not correlate as well as with Japanese DPB patients (44). Among diagnostic tests, a chest CT scan provides the most valuable diagnostic means for such patients.…”
Section: Discussionmentioning
confidence: 73%
“…Hatta et al (60) have recently suggested that this B*54-associated haplotype is particularly common in the Ryukyuan population, who form one of the important ancestral populations of Okinawa and Kyushu in Southern Japan. Associations have also been described between B*5401 and other inflammatory conditions in Japan, including hepatitis C (61, 62) and diffuse panbronchiolitis (63,64). The HLA-associated susceptibility gene associated with diffuse panbronchiolitis has been mapped to a 200-kb region, 300 kb telomeric of the HLA-B locus (65).…”
Section: Figurementioning
confidence: 99%
“…Blood samples of the DPB cases were obtained from the Toranomon Hospital, Tenri Hospital, or Nippon Medical School Hospital, Japan. The diagnostic criteria for DPB proposed in 1995 by a working groups [9] were: 1) persistent cough, sputum, and exertional dyspnoea; 2) past or present history of chronic sinusitis; 3) bilateral diffuse small nodular shadows on a plain chest radiograph film or centrilobular micronodules on chest CT images; 4) coarse crackles; 5) FEV1/FVC v70% and oxygen tension in arterial blood v10.64 kPa (v80 mmHg); and 6) titre of cold haemagglutinin ¡64. A total of 82 DPB patients were recruited for this study and fulfilled criteria 1), 2), 3) and at least two of criteria 4), 5), and 6).…”
Section: Study Subjectsmentioning
confidence: 99%
“…Cases of DPB are mainly found in East Asian populations [7,8], and neither environmental factors nor infections specific to the disease have been demonstrated. It has also been reported that human leukocyte antigen-B alleles or a closely linked gene contribute to genetic predisposition in DPB [9]. After considering these facts, the authors hypothesized that genetic factors may be associated with the pathogenesis of DPB.…”
mentioning
confidence: 99%